2003
DOI: 10.1002/mds.10615
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary late‐onset focal dystonia in the Belgrade population

Abstract: The aim of this cross-sectional study was to estimate the prevalence of different subtypes of idiopathic focal dystonia in the population of Belgrade (Serbia), Yugoslavia. On December 31, 2001, the crude prevalence of all studied types of dystonia (focal, segmental, and multifocal) in Belgrade was 13.6 per 100,000 population (11.8 per 100,000 for men and 15.2 per 100,000 for women). Type-specific prevalence for focal dystonia was 11.2 per 100,000. The prevalence for cervical dystonia, blepharospasm, writer's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
60
5
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 13 publications
11
60
5
1
Order By: Relevance
“…Our estimates are in keeping with other reports [12,15] . Only six studies reported prevalence rates of focal/ segmental dystonia higher than ours.…”
Section: Discussionsupporting
confidence: 82%
“…Our estimates are in keeping with other reports [12,15] . Only six studies reported prevalence rates of focal/ segmental dystonia higher than ours.…”
Section: Discussionsupporting
confidence: 82%
“…Prevalence ratios of women to men have ranged from 1.5 to 3.6:1. [4][5][6][7]16,17 As with differences in incidence by ethnicity, we cannot differentiate health-careseeking patterns from biologic factors as the cause for the observed differences with any certainty. However, we did find a significantly younger age at diagnosis and shorter illness duration prior to diagnosis in men than in women.…”
Section: Figurementioning
confidence: 96%
“…[1][2][3][4][5][6] There have been two previous estimates of the incidence of this disorder, and both were performed in populations of largely European descent. 7,8 There are no published estimates from ethnically diverse populations.…”
mentioning
confidence: 99%
“…Risk and protective factors are correlational and not causal. Based on a review of the literature, genetic factors, including autosomal dominant traits with reduced penetrance, or alternatively polygenic inheritance may predispose individuals to dystonia development [12][13][14][15] ; however, repetitive attended fine motor movements involving the affected limb or structure may trigger or localize the dystonia. [16][17][18] Additionally, head, neck, trunk, or limb trauma, ocular diseases, and social anxiety/phobias have also been linked to adult-onset dystonia.…”
Section: Introductionmentioning
confidence: 99%